2020
DOI: 10.3390/ma14010108
|View full text |Cite
|
Sign up to set email alerts
|

Critical Influence of the Processing Route on the Mechanical Properties of Zirconia Composites with Graphene Nanoplatelets

Abstract: Graphene-based nanostructures, used as potential reinforcement in ceramic composites, have a great tendency to agglomerate. This requires the use of homogenization techniques during the powder processing, posing the need to evaluate how these techniques affect the microstructure and the mechanical properties of the resulting composites. The influence of the processing route on the properties of 3YTZP (3 mol % yttria tetragonal zirconia polycrystals) ceramic composites with 10 vol % cost-effective GNP (graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In relation to the matrix, all the composites exhibited sub-micrometric equiaxed zirconia grains as reported elsewhere [38,49,58]. Table 2 shows the mean grain size and standard deviation of the lognormal distribution of the ceramic grains.…”
Section: Microstructural Characteristics Of the Zirconia/mlg Compositessupporting
confidence: 68%
“…In relation to the matrix, all the composites exhibited sub-micrometric equiaxed zirconia grains as reported elsewhere [38,49,58]. Table 2 shows the mean grain size and standard deviation of the lognormal distribution of the ceramic grains.…”
Section: Microstructural Characteristics Of the Zirconia/mlg Compositessupporting
confidence: 68%
“…With the increase of GDs content, the mechanical properties of composite materials show a trend of increasing at first and then decreasing (Du et al, 2020). In addition, different interface binding modes (Compton et al, 2012;Park et al, 2008), oxygen content in GO (Maldonado-Magnere et al, 2020), and different manufacturing processes (Gallardo-Lopez et al, 2020) can affect the mechanical properties of graphene composites, which makes the mechanical properties of graphene composites tunable. Therefore, it is theoretically possible for GMs to mimic the properties of bone, which is extremely exciting in bone tissue engineering.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Various studies have found that the mechanical properties of graphene and its derivatives are affected by different interface binding modes, oxygen content, and different manufacturing processes, which makes the mechanical properties of graphene and its derivatives adjustable [ [40] , [41] , [42] ]. Therefore, graphene and its derivatives can theoretically mimic the mechanical properties of human bone and have broad prospects in the field of bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%